2023
DOI: 10.1002/1873-3468.14685
|View full text |Cite
|
Sign up to set email alerts
|

The secret life of chromatin tethers

Abstract: The nuclear envelope plays an essential role in organizing the genome inside of the nucleus. The inner nuclear membrane is coated with a meshwork of filamentous lamin proteins that provide a surface to organize a variety of cellular processes. A subset of nuclear lamina‐ and membrane‐associated proteins functions as anchors to hold transcriptionally silent heterochromatin at the nuclear periphery. While most chromatin tethers are integral membrane proteins, a limited number are lamina‐bound. One example is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 67 publications
(118 reference statements)
0
3
0
Order By: Relevance
“…Consistent with this hypothesis, Lamin B Receptor (LBR) mediates at least in part the peripheral positioning of heterochromatin 63,64 and was shown to preferentially interact with supercoiled DNA 65 . Specific concentration of factors such as HP1 or modified histones could also mediate anchoring of boosting regions at the NL 22,66 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this hypothesis, Lamin B Receptor (LBR) mediates at least in part the peripheral positioning of heterochromatin 63,64 and was shown to preferentially interact with supercoiled DNA 65 . Specific concentration of factors such as HP1 or modified histones could also mediate anchoring of boosting regions at the NL 22,66 .…”
Section: Discussionmentioning
confidence: 99%
“…How are LAD-NL interactions instructed by LAD DNA ? Although several chromatin and NL proteins have been identified that may mediate NL-LAD interactions 21,22 , a major unresolved question is how these interactions are encoded within LAD DNA. This is particularly intriguing considering the enormous size of LADs.…”
Section: Introductionmentioning
confidence: 99%
“…The last term captures the interaction between chromatin and the nuclear lamina, which leads to the formation of LADs along the nuclear periphery. In-vivo, the interactions between chromatin and the nuclear lamina are orchestrated by a diverse set of chromatin anchoring proteins, such as LAP2β, LBR, emerin and PRR14, associated with the inner nuclear membrane and the nuclear lamina [10,17]. While these interactions can be individually incorporated by capturing the strength of each anchoring protein associated with the lamina and the nuclear membrane, as a first approximation we assume these to be the same.…”
Section: Driving Forces For the Spatiotemporal Evolution Of Chromatinmentioning
confidence: 99%
“…The article by Capelson [10] explores how nucleoporins affect gene expression, focusing on the fact that a subset of nucleoporins can localize to the nuclear interior and interact with chromatin through a variety of associated chromatin‐modulating proteins, thus contributing to the gene expression control on multiple levels. The role of the nuclear periphery in the organization of heterochromatin in mammals is discussed by Kiseleva and Poleshko [11], while Buxboim et al . [12] provide the latest insights into the structural organization of the lamina, in particular its major constituents, the nuclear lamins.…”
mentioning
confidence: 99%